A Study of Curiosity among School Children in Relation to Intelligence and Scholastic Achievement - Dr. Vaishaliben Bhogilal Patel (International Journal on Integrated Education, 2022)
Children, by nature, are active, restless and have an urge to touch, feel, experience and understand everything Anything that is new to them or that bas motion attracts their attention. Their inquisitiveness seems to be insatiable. Investigations in human curiosity are relatively new. In view of the paucity of researches in this area, the present investigation distinguishes itself by taking a large sample with gender as well as rural-urban differences taken into consideration. It finds out correlations between curiosity, intelligence, and scholastic achievement and also differentiates between the high and low curiosity children in respect of intelligence and scholastic achievement. The study arrives at interesting findings, important for educational practitioners at the school level.